If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12c + -6 = 10c + 4 Reorder the terms: -6 + 12c = 10c + 4 Reorder the terms: -6 + 12c = 4 + 10c Solving -6 + 12c = 4 + 10c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-10c' to each side of the equation. -6 + 12c + -10c = 4 + 10c + -10c Combine like terms: 12c + -10c = 2c -6 + 2c = 4 + 10c + -10c Combine like terms: 10c + -10c = 0 -6 + 2c = 4 + 0 -6 + 2c = 4 Add '6' to each side of the equation. -6 + 6 + 2c = 4 + 6 Combine like terms: -6 + 6 = 0 0 + 2c = 4 + 6 2c = 4 + 6 Combine like terms: 4 + 6 = 10 2c = 10 Divide each side by '2'. c = 5 Simplifying c = 5
| 3a+11=4a+8 | | 4/5x+3=5x | | 4g-9=(-3g)+12 | | 2/3(3x+12)=32 | | 3(x+5)+4=3x+4 | | .2x^2+16x=0 | | 42=-6(-2x-3) | | 5(2x+3)-2=-2(x+4) | | 6(7x+3)=354 | | -3/7x+4 | | M/2=m-2/3 | | 4(-2x-5)=-76 | | 3p=9p-12 | | (15,625a^-18b^3c^24)^1/6 | | x^3-5x+12=0 | | x^3+5x-12=0 | | 25x-400+28x+90=3061 | | 2x-2.2=8.4 | | -5x-8=-58 | | 7a-4=2a+16 | | 7-(2x+5)=18-8x | | x^6=726 | | 3x+5+6x-7=25-x | | 5+(3x+6)/5+x | | 2n+7=11-2n | | b^2+4b-12/2b^2-18 | | 8=3y+5y-24+16 | | 20=4m/9 | | -1/2x=14 | | 3x+13=-x-15 | | 5x-15=7x+25 | | -5=4x-21 |